Rancangan Teknologi Tepat Guna untuk Mesin Penggiling Kopi Sistim Poros Vertikal - Alfian - - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2018)
Coffee is material of drink and coffee income for Indonesia Country. Each one of coffee proses for drink is grind proses. Grind coffee proses influence of taste and confortable. The grind coffee prosesto produce powder, natural aroma, big capacity, easily found, estetika, and economic value. From research, hoper the grind coffee machine is the produce coffee powder, natural aroma, capacity, small power electrical, portable, estetika and economic value.In this paper Grinder Coffee Machine Vertical Shaft System, to produce grinder with Conical Burr Grinder so natural aroma, powder smoot and same size. The specification this machine is power 0.5 HP, motor rotation 500 rpm, size 300mm x 300mm x 470mm and capacity produce 106 kg/hour.